A Baseline Study of Strategies to Promote Critical Thinking in the Preschool Classroom (GIST – Education and Learning Research Journal, 2015)
The purpose of this study was to identify the different incidents of critical thinking in five preschool classrooms in one school, and the instructional strategies preschool teachers employed in the development of children’s critical thinking. The participants in this study were five self-contained preschool teachers and their corresponding groups. The study explored teachers’ beliefs in regards to the role of critical thinking in their classrooms. Data collection techniques included classroom observations, document analysis, and interviews with teachers. Two over-arching findings include: a) it is possible to observe and describe numerous instances in which critical thinking is paid attention to explicitly by teachers, and b) it is possible to observe a range of classroom interactions and techniques that explicitly develop these skills among preschoolers.
Keywords: Critical thinking; instructional strategies; classroom interactions; preschoolers; teachers’ beliefs; development of thinking.